Disgust-induced attentional blink at Lag3: a diagnostic and therapeutic approach to depression - Wang, Yingying; Wang, Qi; Chen, Lijie; Dong, Xiaomei; Xu, Tianchao (Frontiers in Psychiatry, 2025)
BackgroundCognitive impairment, particularly in attention, are recognized as key diagnostic indicators of depression. However, the use of the Emotional-Induced Attentional Blink paradigm to assess attentional deficits in depression has not been fully explored.MethodsThis study included 32 mildly depressed, 32 severely depressed, and 32 healthy control participants recruited between March and December 2023. Participants’ attention was assessed by measuring their ability to recognize targets, while emotional faces (disgust, fear, sadness, and neutral) acted as distractors, with lags of 100ms, 300ms, and 700ms before the target.ResultsThe results indicated that disgusted faces caused greater attentional impairment in depressed patients, resulting in a stronger attentional blink effect. The impact of these emotional stimuli is correlated with the severity of depression. Notably, the attentional blink effect at the 300ms lag with disgust faces (D3) was a strong predictor of depression severity. Receiver Operating Characteristic (ROC) analysis showed the Area Under the Curve (AUC) values for no depression, mild depression, and severe depression to be 0.75, 0.61, and 0.73, respectively.ConclusionThese findings suggest that the attentional blink effect with disgusted faces at the 300ms lag can serve as a useful tool for identifying and assessing depression, as well as a potential target for attentional bias modification training in depression treatment.